Proceedings of the 8th International Nursing Conference on Education, Practice and Research Development in Nursing (INC 2017) 2017
DOI: 10.2991/inc-17.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Men's Participation to Support Early Detection of Cervical Cancer in Indonesia: A Literature Review

Abstract: Abstract-The number of cervical cancer patients in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…7 Low male involvement may result in fewer national screening. 8 Men have a role in reducing cervical cancer burden by supporting their spouses financially, encouraging them to get screened, and provide emotional support. 9 However, studies conducted in Swaziland, Ghana, and Kenya revealed that men had a limited understanding of cervical cancer and lacked awareness of risk factors, causes, signs, prevention, and treatment.…”
mentioning
confidence: 99%
“…7 Low male involvement may result in fewer national screening. 8 Men have a role in reducing cervical cancer burden by supporting their spouses financially, encouraging them to get screened, and provide emotional support. 9 However, studies conducted in Swaziland, Ghana, and Kenya revealed that men had a limited understanding of cervical cancer and lacked awareness of risk factors, causes, signs, prevention, and treatment.…”
mentioning
confidence: 99%